2021
DOI: 10.31098/ijebce.v1i1.423
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants Factors of Womenpreneurship Performances in Low Economic Class : An Evidence from Melaka

Abstract: Within this study, we want to examine factors those determine to the rise of womenpreneurship, since it is one of the most important 2030 Agenda for Sustainable Development to eradicate national poverty as well as to support the innovation and ever-growing economy. The increasing of women's participation in entrepreneurs demonstrated positive impact of female entrepreneurs, not only on the family but also on economic growth and development. We build our theoretical framework based on literature surveys; that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…With the high growth in women entrepreneurs in developing nations, a critical area for further investigation is identifying how these women develop social capital, alternate business channels, newer market opportunities, and new technological skills. Several recent studies [69][70][71][72][73][74] indicate digitization and the adoption of e-commerce as critical for the survival of women entrepreneurs, but examining such issues more closely from a socio-political lens may help to identify challenges related to developing-country idiosyncrasies. Institutional voids and socio-cultural barriers may also vary across different countries, and the increasing research undertaken in more developing countries provides opportunities for more cross-country comparisons.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…With the high growth in women entrepreneurs in developing nations, a critical area for further investigation is identifying how these women develop social capital, alternate business channels, newer market opportunities, and new technological skills. Several recent studies [69][70][71][72][73][74] indicate digitization and the adoption of e-commerce as critical for the survival of women entrepreneurs, but examining such issues more closely from a socio-political lens may help to identify challenges related to developing-country idiosyncrasies. Institutional voids and socio-cultural barriers may also vary across different countries, and the increasing research undertaken in more developing countries provides opportunities for more cross-country comparisons.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…It was revealed that 64 per cent of the respondents experienced a lack of capital and 55 per cent of them stated that they faced difficulty in getting a loan from the government and private sector. Hence, it is crucial for governments to continuously provide a supportive business environment to accommodate the international growth and development of women SMEs in Malaysia (Malik et al, 2021;Wahid et al, 2021). In the context of Tanzania, Isaga (2019) explored the challenges confronted by women entrepreneurs by distributing semi-structured questionnaires and conducting in-depth interviews with 20 research participants.…”
Section: Financial Limitationsmentioning
confidence: 99%